2010
DOI: 10.1037/a0019673
|View full text |Cite
|
Sign up to set email alerts
|

Fear and anger reactivity trajectories from 4 to 16 months: The roles of temperament, regulation, and maternal sensitivity.

Abstract: Two goals guided this study: (a) describe changes in infant fear and anger reactivity from 4 to 16 months and (b) examine the degree to which infant temperament, attentional regulation, and maternal sensitivity predict reactivity trajectories. Participants included 143 mothers and infants (57% male) who visited the laboratory at 4, 8, 12, and 16 months. Infant reactivity, regulation, and maternal sensitivity were assessed from laboratory situations; infant temperament was rated by mothers on the Infant Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 64 publications
6
126
1
8
Order By: Relevance
“…This profile of temperament characteristics may improve the survival of young infants according to the evolutionary framework underlying fetal programming via PNMS. Fearfulness may protect the infants by priming them to avoid danger in potentially harmful environments (Bergman et al, 2007; Braungart-Rieker et al, 2010). Greater sensitivity, and reactivity might enable the child to more efficiently sense potential threats and elicit parental attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This profile of temperament characteristics may improve the survival of young infants according to the evolutionary framework underlying fetal programming via PNMS. Fearfulness may protect the infants by priming them to avoid danger in potentially harmful environments (Bergman et al, 2007; Braungart-Rieker et al, 2010). Greater sensitivity, and reactivity might enable the child to more efficiently sense potential threats and elicit parental attention.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, researchers have found that “difficult” temperament, including low rhythmicity, withdrawal responses, low adaptability, negative mood and high-intensity of reactions, follows a nonlinear developmental trajectory, increasing around ages 2–3, and decreasing linearly from toddlerhood to preschool (Partridge and Lerner, 2007). Data also suggests that negative affect, such as fearfulness and anger, increases with age from 4 to 16 months (Braungart-Rieker et al, 2010). Some studies show that effortful control (e.g., attention and orienting), which modulates negative emotionality and reactivity, begins to develop by the end of the first year of life (Posner and Rothbart, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not until the age of 7 mo that they show a robust attentional bias to fear, as reflected in their neural and behavioral responses (37)(38)(39)(40)(41). The developmental emergence of this fear bias has been linked to the maturation of frontolimbic circuits (42)(43)(44)(45) and occurs at a point in development when infants begin to first experience fear themselves (46,47). Despite our growing understanding of the developmental origins of emotion and gaze processing in humans, some fundamental questions concerning the exact nature of this ability remain unanswered.…”
Section: Significancementioning
confidence: 99%
“…Anger expression is already observed in infancy (Braungart-Rieker, Hill-Soderlund, & Karrass, 2010;Pemberton Roben et al, 2012), and the structure of anger is universal across cultures (Alonso-Arbiol et al, 2011). Because people express anger under interpersonal provocations or conflicts, rapid recognition of angry faces is important to restore relationships with others or to be motivated to avoid dangerous situations.…”
Section: The Influence Of Working Memory On the Anger Superiority Effectmentioning
confidence: 99%